The dreamgivers - Walker, James, 1948- (Minneapolis, Minn. : Bethany House Publishers, 1994)
Zachary Cobb came from West carry the bitter memories and scars the battle left in his soul. Yet the skills developed in battle now serve Zac well as an undercover agent for Wells Fargo. When Jenny Hays, the young woman who cares for Zac, is unwittingly drawn into the final confrontation, he finds himself facing danger from without and within.
Sequel: The nightriders.
Keywords: Wells, Fargo & Company -- Fiction; Fronter and pioneer life-west; Walker, Janes; Wells Fargo trail; Christian fiction; Western stories